2021
DOI: 10.1093/aje/kwab106
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2 Case Definitions for Ascertaining the Prevalence of Autism Spectrum Disorder Among 8-Year-Old Children

Abstract: The Autism and Developmental Disabilities Monitoring (ADDM) Network conducts population-based surveillance of autism spectrum disorder (ASD) in multiple US communities among 8-year-old children. To classify ASD, ADDM sites collected text descriptions of behaviors from medical and educational evaluations which were reviewed and coded by ADDM clinicians. This process took at least four years to publish data from a given surveillance year. In 2018, we developed an alternative case definition utilizing ASD diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 17 publications
1
18
0
1
Order By: Relevance
“…The previous ASD case definition was based on operationalized criteria described in DSM-5 and involved detailed abstraction and expert clinical review of behavioral symptoms documented in children’s evaluations ( 1 ). An analysis using data from ADDM Network surveillance years 2014 and 2016 compared the case definitions and found that, compared with the overall ASD prevalence using the previous case definition, ASD prevalence using the new case definition was approximately the same for 2014 and 7% lower for 2016 ( 12 ). Other indicators, such as prevalence ratios, ages at evaluation or ASD diagnosis, and co-occurring intellectual disability, were similar using both case definitions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous ASD case definition was based on operationalized criteria described in DSM-5 and involved detailed abstraction and expert clinical review of behavioral symptoms documented in children’s evaluations ( 1 ). An analysis using data from ADDM Network surveillance years 2014 and 2016 compared the case definitions and found that, compared with the overall ASD prevalence using the previous case definition, ASD prevalence using the new case definition was approximately the same for 2014 and 7% lower for 2016 ( 12 ). Other indicators, such as prevalence ratios, ages at evaluation or ASD diagnosis, and co-occurring intellectual disability, were similar using both case definitions.…”
Section: Discussionmentioning
confidence: 99%
“…The ADDM Network is an active records-based surveillance program using multiple sources of information within a community ( Table 1 ). For surveillance year 2018, the ADDM Network adopted a case definition and data collection process and method to fit the increased availability of ASD diagnostic information in health and education records ( 12 ). As with the previous methods, which were based on the model created by CDC’s Metropolitan Atlanta Developmental Disabilities Surveillance Program ( 13 ), sites request records (electronic and paper-based) from community medical, education, and service providers containing specific special education exceptionalities or billing codes from the International Classification of Diseases, Ninth Revision (ICD-9) or International Classification of Diseases, Tenth Revision (ICD-10).…”
Section: Methodsmentioning
confidence: 99%
“…ADDM will continue to incorporate chart review; however, ASD ascertainment will reflect ASD diagnoses or classifications from various medical, educational, and service providers in each participating community. An analysis comparing the previous and new case definitions showed the two produced similar ASD prevalence estimates, and other indicators were essentially unchanged ( 161 ). The changes enabled ADDM sites to incorporate a wider range of data sources (such as state Medicaid programs), allowed for expanded tracking of early ASD identification among children aged 4 years, and allowed sites to begin reporting on the medical issues, mental health issues, and challenges with the transition to adulthood among children aged 16 years with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons with previous reports among children aged 4 years were limited by small numbers among non-White groups in surveillance year 2010 and a lack of aggregate estimates for surveillance years 2012 and 2014 ( 13 ). A change to the ASD case definition for 2018 that no longer required clinician review of records ( 12 ) could also contribute to higher prevalence among Black and Hispanic children who were less likely to have detailed health information available for review and therefore less likely to meet the case definition with previous methods ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Children met the surveillance ASD case definition if they were aged 4 years in 2018 (born in 2014), had a parent or guardian living in the surveillance area for at least one day during 2018, and had ever received a written ASD diagnostic statement (diagnosis) by a qualified professional, a special education classification of ASD (eligibility), or an ASD ICD-9 code between 299.00 and 299.99 or an ICD-10 code in the F84 range ( 12 ). Children with an ICD code for F84.2 (Rett syndrome) and no other indicators of ASD did not meet the ASD case definition.…”
Section: Methodsmentioning
confidence: 99%